Stigma associated with living in a care home: perspectives of older residents living in care homes in Thailand - Tosangwarn, Suhathai; Clissett, Philip; Blake, Holly (2017)
Background: High prevalence of depression has been reported among older adults living in care homes in Thailand, associated with physical impairment, low social support, low self-esteem and particularly stigma associated with living in a care home. However, little is understood about how such stigma is experienced among Thai care home residents. This study examines residents’ perceptions of stigma and their strategies for coping with stigma. Method/Design: Case study research was used to gain an in-depth view about stigma of residents’ perspectives and experiences from two care homes in the northeast of Thailand by conducting an in-depth interview and non-participant observation. Qualitative interviews were conducted with 30 older residents (aged >60 years), purposively sampled from both care homes. Non-participant observation was conducted in various public spaces of the care homes, including the dining room, corridors, and activities areas for approximately one to two hours per day at different times; morning and afternoon including weekdays and weekend in both care homes for one month. Thematic analysis was used to analyse the data. Results: The study identified three major themes related to the causes of stigma, the reactions towards stigma and the mitigating factors. Negative beliefs about care homes, negative attitudes and stereotypes toward the elderly and perceptions of unequal power relations between staff and residents were the main factors precipitating stigma. Consequently, residents exhibited negative emotions and behaviours, including depressive symptoms, while living in care homes. Residents reported the use of particular coping strategies, including accessing support from the public and staff, and engaging in care home activities which these helped them to cope with their perception of stigma. Conclusion: Improved understanding of the underlying factors behind perceived stigma in care home residents may help to prevent depression and reduce perceptions of stigma associated with living in a care home, by informing strategy, supportive intervention and guidelines for appropriate care for older Thai residents.